A hospital-based screening, referral, and follow-up program for high blood pressure. - Theisen, V (1979)
A hypertension program staffed largely by volunteer nurses in a hospital outpatient department is described. A three-year evaluation shows 19% of 4,282 clients screened as having high readings, 86% of those referred saw a physician for high blood pressure, 92% of those who saw a physician began treatment for high blood pressure and 50% of those under treatment were showing successful control or progress toward successful control.